2009
DOI: 10.1371/journal.pone.0007115
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Antiretroviral Therapy in a Cohort of HIV Infected Patients Going in and out of the San Francisco County Jail

Abstract: BackgroundJails are an important venue of HIV care and a place for identification, treatment and referral for care. HIV infected inmates in the San Francisco County jail are offered antiretroviral treatment (ART), which many take only while in jail. We evaluated the effect of ART administration in a cohort of jail inmates going in and out of jail over a nine year period.Methodology/Principal FindingsIn this retrospective study, we examined inmates with HIV going in and out of jail. Inmates were categorized by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
7
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(8 citation statements)
references
References 12 publications
1
7
0
Order By: Relevance
“…Its disruption of social networks independently increases risk of HIV transmission, 8 and, for people living with HIV who are prescribed antiretroviral therapy (ART), reincarceration is associated with interruptions in medication adherence and persistence (duration of time from inititation to discontinuation of therapy). 912 Although we reported that 70% of inmates with HIV in Connecticut achieved viral suppression during incarceration, 13 we expected on the basis of historical data in this setting 14 and elsewhere 1518 that viral suppression would not persist after release despite simpler, more potent, and better tolerated ART regimens.…”
Section: Introductionmentioning
confidence: 93%
“…Its disruption of social networks independently increases risk of HIV transmission, 8 and, for people living with HIV who are prescribed antiretroviral therapy (ART), reincarceration is associated with interruptions in medication adherence and persistence (duration of time from inititation to discontinuation of therapy). 912 Although we reported that 70% of inmates with HIV in Connecticut achieved viral suppression during incarceration, 13 we expected on the basis of historical data in this setting 14 and elsewhere 1518 that viral suppression would not persist after release despite simpler, more potent, and better tolerated ART regimens.…”
Section: Introductionmentioning
confidence: 93%
“…Criminal justice (CJ) settings are highly structured and can be positioned to diagnose, engage, and treat PLH with antiretroviral therapy (ART), which reduces within-prison morbidity and mortality (4, 5). Short-term detentions within and release from jails, however, are destabilizing and can undermine HIV treatment outcomes (68). Recidivism is often influenced by untreated SUDs and psychiatric disorders and can also negatively impact engagement in HIV care, resulting in suboptimal viral suppression (57, 9).…”
Section: Introductionmentioning
confidence: 99%
“…Previous research confirms that the benefits afforded by ART within prison are rarely sustained after release (913). These issues have not yet been fully explored among released jail detainees, but available data suggest that as few as 14% of jail recidivists receive continuous ART (14), a number that is similar to those reported for released HIV-infected prisoners.…”
Section: Introductionmentioning
confidence: 99%